In memoriam - Dr Cobus Badenhorst - Vorster, Jean (SA Heart Journal, 2026)
Dr Cobus Badenhorst passed away on 27 October 2025 after a short and traumatic illness. It happened too unexpectedly and too soon, leaving his family, friends, colleagues, and patients in deep shock and sorrow.